Dynamics of offshore risers using a geometrically-exact beam model with hydrodynamic loads and contact with the seabed. (15th October 2016) - Gay Neto, Alfredo
Highlights: This work presents a geometrically-nonlinear model to simulate offshore risers' dynamics. Rodrigues rotation parameters were used to describe rotations, assuming an updated-Lagrangian scheme. The consistent linearization of the weak form contribution due to hydrodynamic loads was obtained, using Morison's model. The Newton-Raphson method was used to solve risers' dynamics using an implicit time-integration scheme. The riser-seabed interaction was considered with a model that accounts for the possibility of riser rolling on the seabed. Abstract: In the context of challenging scenarios for offshore oil exploitation, robust numerical models are necessary to predict the risers' mechanical behavior. This work presents a model to simulate offshore risers' dynamics using the geometrically-exact approach for beams. Expressions are derived for the hydrodynamic loads due to riser-seawater flow interaction, adopting the Morison's equation and considering large displacements and finite rotations, including the added mass and drag contributions. The consistent linearization of the weak form of such effects was obtained, permitting the use of Newton-Raphson method to solve risers' dynamics using an implicit time-integration scheme. The riser-seabed interaction is also considered with a model that accounts for the possibility of rolling on the seabed. A catenary riser dynamics and a vertical riser experiencing parametric resonance due to heave-imposed motion were simulated. The model showed promising behavior to deal with large nonlinearities.